Democracy and community participation in health services - León Pretel, Pricila (2020)
The article gives an account of community participation in the co-management of health services in the Local Community of Health Administration (CLAS) San Martin de Porres. The objective of the research has been to identify the achievements of citizen participation in relation to representativeness, a major element in the democratization and decentralization of health services in Peru. The methodology includes: participating observation, survey of 107 people of the human settlement by questionnaire, structured interview with 3 presidents of the CLAS San Martin de Porres and analysis of experiences at the national level. The results show that the targeted policy, implemented by the State since 1994, does not promote the democratic participation of the population in health services. Participation is controlled and aimed at seeking efficiency and equity in the management of health services, rather than democratic exercise as a purpose. In practice, it is found that the way in which health policy has been designed does not guarantee such participation.